Patient perceptions of the re-usable Respimat® Soft Mist™ inhaler in current users and those switching to the device: A real-world, non-interventional COPD study. (28th January 2021) - Dreher, Michael; Price, David; Gardev, Asparuh; Peeters, Pascale; Arora, Satish; van der Sar – van der Brugge, Simone; Dekhuijzen, Richard; Usmani, Omar S
The Respimat ® Soft Mist™ inhaler (SMI) has recently been improved, with a re-usable device replacing the disposable version. Certain countries are currently phasing out the disposable inhaler. This study aimed to assess patient satisfaction with and preference for the re-usable device. This 4–6-week, multicentre, open-label, prospective, real-world, non-interventional study was conducted across six European countries. Patients with chronic obstructive pulmonary disease were enrolled between October and December 2019, in three cohorts: (1) currently using the re-usable Respimat SMI; (2) switched from disposable Respimat SMI at study entry; and (3) naïve to any Respimat SMI. Patients were assessed using the Patient Satisfaction and Preference Questionnaire (PASAPQ) and Ease of Handling Questionnaire. In total, 262 patients were enrolled. At follow-up, the mean PASAPQ score was 83.3/100 overall, with similar results across all three patient cohorts. Most patients were 'satisfied' or 'very satisfied' with the re-usable device. The overall score for willingness to continue using the device was 87.8/100. In total, 13 adverse events were recorded, none of which was classified as serious. This study provides real-world evidence for practitioners to start patients on Respimat re-usable, irrespective of a patient's prior experience with this inhaler. Plain language summary: Inhalers are often used to treat patients with chronic obstructive pulmonary disease (COPD). However, there are many available, which can lead to confusion and poor inhaler technique. It is important for a patient to be happy with their inhaler. This study looked at how patients liked the re-usable Respimat® Soft Mist™ inhaler vs. their previous inhaler. It also asked whether they would be willing to continue using the device at the end of the study period.After 4–6 weeks of using the re-usable device, patients reported that they were happy with the inhaler and most would be willing to carry on using it.Overall, these results show that doctors can prescribe Respimat re-usable to patients, even if the patient has not used the inhaler before.